Value Creation in European Equity Carve-Outs - Pojezny, Nikolas; SpringerLink (Online service) (Wiesbaden : DUV, 2006)
The total volume of equity carve-outs (i.e. IPOs of subsidiary firms) in Europe over the last 20 years amounts to approx. € 90 billion. Carve-outs thus account for almost 20% of the total IPO volume. Companies use them for a variety of reasons aimed at increasing shareholder value. Nevertheless, not all carve-outs actually do create value. Employing the most comprehensive sample of European carve-outs to date, Nikolas Pojezny analyzes the performance of carve-outs along various dimensions: Both the reaction of parent firms to the announcement of a carve-out as well as share price and operating performance in a multi-year window around the event are examined in detail. While the announcement of carve-outs on average causes positive share price reactions for parent firms, long-term performance is mixed: Evidence for both earnings management and market timing is found, with negative implications for long-term performance. The potential for value creation increases in the relative discrepancy level between internal and external capital markets. The second event decision seems mainly driven by the valuation level of the subsidiary, industry association, initial stake sold, and development state of external capital markets.
Definitions and theoretical foundations -- Short-term price performance of European equity carve-outs -- Long-term operating performance of European equity carve-outs -- Long-term price performance of European equity carve-outs -- What do we learn about internal capital markets from equity carve-outs? -- Determinants of the nature of the second event in European equity carve-outs -- Conclusion.
Keywords: Finance; Finance; Finance, general; Electronic books